Knowledge spillovers, knowledge filters and entrepreneurial university ecosystems. Emerging role of University-focused venture capital firms. Issue 1 (2nd January 2021) - Padilla-Meléndez, Antonio; Fuster, Elena; Lockett, Nigel; del-Aguila-Obra, Ana Rosa
ABSTRACT: In this study, we analyse the role played by investment managers from University-focused Venture Capital firms (UVCs) in knowledge spillovers in Entrepreneurial University Ecosystems (EUEs). Data from fifteen in-depth interviews with key agents of the EUEs in England was examined through the lens of the Knowledge Spillover Theory of Entrepreneurship, using Social Network Analysis and qualitative analysis. We identified the emerging role of UVCs as key knowledge intermediaries in developing and sustaining EUEs, concluding that UVCs are key to overcoming knowledge filters and maintaining dynamic relationships over time between entrepreneurial universities and University Spin-off companies. In this paper, we describe how UVCs act as social connectors, facilitating a two-way knowledge and technology exchange necessary in the development and sustainment of EUEs.